Peran Integritas dan Teamwork Dalam Upaya Peningkatan Efektivitas Kerja Pegawai - Nepi Andriani (Pusat Riset dan Inovasi Nasional, 2024)
This research investigates the role of employee integrity and teamwork in increasing work effectiveness in government organizational environments. The research methods used include identifying important factors, building a cultural integration model, analyzing positive impacts, identifying research gaps, and preparing practical recommendations. The research results show that employee integrity and good teamwork have a significant impact on increasing performance, adaptability, innovation, employee satisfaction and reducing conflict in government organizations. However, there are research gaps related to the lack of empirical studies, variations in organizational contexts, the influence of technology, implementation strategies, and measurement and evaluation. As practical recommendations, training and development, exemplary leadership, rewards and recognition, supportive policies and procedures, effective communication, use of technology, regular evaluation and conflict handling are needed. This research's contribution to the literature covers various fields of study such as public management, organizational studies, work and organizational psychology, and policy development. The findings of this research provide practical implications that can help government organizations improve their performance and effectiveness in providing quality public services.